Revisiting the Needham Puzzle and Contemporary Chinese Society - Bhattacharjee , Mowsume (The National University Journal of Humanities, Social Sciences and Business Studies, 2023)
The Needham puzzle is: Why did China fail to originate the scientific-industrial revolution before England? This paper aims to revisit Joseph Needham's work by identifying the reasons behind the expansion of modern science in Europe rather than China despite the revolutionary technical achievements of then China. The central research question of this study is: How relevant is the Needham puzzle to explain the recent development of Chinese society in relation to science and technology? Following the research question, this paper draws primarily on secondary data collecting information from published and unpublished research works. This paper developed an analytical framework to explain the Needham puzzle and examines the recent trends of Chinese development with a special focus on the domain of science and technology. In conclusion, this paper revisits the Needham puzzle and, based on the analytical framework, finds that the Needham puzzle is relatively less relevant to explain the socioeconomic, political, religious, scientific, and technological development of contemporary Chinese society. NU Journal of Humanities, Social Sciences & Business Studies Vol. 7 & 8, No.2 & 1, July 2021 - December 2022 p. 75-97